Aproveitamento da fibra do epicarpo do coco babaçu em compósito com matriz epóxi: estudo do efeito do tratamento da fibra - Franco, Francisco José Patrício (2010)
Nowadays the environmental issues are increasingly highlighted since the future of humanity is dependent on the actions taken by man. Major efforts are being expended in pursuit of knowledge and alternatives to promote sustainable development without compromising the environment. In recent years there has been a marked growth in the development of reinforced composite fiber plants, as an alternative for economic and ecological effects, especially in the substitution of synthetic materials such as reinforcement material in composites. In this current study the chemical- physical or (thermophysics )characteristics of the babassu coconut fiber, derived from the epicarp of the fruit (Orbignyda Phalerata), which the main constituents of the fiber: Klason lignin, insoluble, cellulose, holocellulose, hemicellulose and the content of ash and moisture will be determined. A study was conducted about the superficial modification of the fibers of the epicarp babassu coconut under the influence of chemical treatment by alkalinization, in an aqueous solution of NaOH to 2.5% (m/v) and to 5.0% to improve the compatibility matrix / reinforcement composite with epoxy matrix. The results of the changes occurred in staple fibers through the use of the techniques of thermogravimetric analyses (TG) and differential scanning calorimetry (DSC). The results found on thermal analysis on samples of fiber without chemical treatment (alkalinities), and on fiber samples treated by alkalinization show that the proposed chemical treatment increases the thermal stability of the fibers and provides a growth of the surface of area fibers, parameters that enhance adhesion fiber / composite. The findings were evaluated and compared with published results from other vegetable fibers, showing that the use of babassu coconut fibers has technical and economic potential for its use as reinforcement in composites